Step-by-step explanation:
Here we have , f(x) = -2.5x + 12; g(x) = 21x - 28 or [tex]f(x) = -2.5x + 12, g(x) = 21x - 28[/tex] .
10. Find h(x) = f(x) + g(x).
⇒ [tex]h(x) = f(x) +g(x)[/tex]
⇒ [tex]h(x) = ( -2.5x + 12)+( 21x - 28)[/tex]
⇒ [tex]h(x) = ( 21x-2.5x )+( 12 - 28)[/tex]
⇒ [tex]h(x) = 18.5x-16[/tex]
11. Find h(x) = g(x) – f(x).
⇒ [tex]h(x) = g(x)-f(x)[/tex]
⇒ [tex]h(x) = ( 21x - 28)-( -2.5x + 12 )[/tex]
⇒ [tex]h(x) = ( 21x+2.5x )+( -12 - 28)[/tex]
⇒ [tex]h(x) = 23.5x-40[/tex]
12. Find h(x) = 4g(x).
⇒ [tex]h(x) = 4g(x)[/tex]
⇒ [tex]h(x) = 4( 21x - 28)[/tex]
⇒ [tex]h(x) = (84x-112)[/tex]